2016
DOI: 10.1175/mwr-d-15-0214.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixture-Based Path Clustering for Synthesis of ECMWF Ensemble Forecasts of Tropical Cyclone Evolution

Abstract: In this article, three tropical cyclones and their 120-h, 50-member ECMWF Integrated Forecasting System (IFS) ensemble track forecasts at 10 initialization times are considered. The IFS forecast tracks are clustered with a regression mixture model, and two traditional diagnostics (the Bayesian information criterion and a measure of strength of cluster assignment) are used to determine the optimal polynomial order and number of clusters to use in the model. In addition, cross-validation versions of the two diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Although optimal cluster characteristics vary forecast-to-forecast, results across all forecasts are examined to select a single combination of polynomial order and number of clusters to evaluate. For mixturemodel clustering of ensemble TC tracks, Kuruppumullage Don et al (2016) and Kowaleski and Evans (2016) found that selecting the optimal polynomial order is more straightforward than selecting the optimal number of clusters; therefore, we evaluate polynomial order first.…”
Section: Clustering Methodologymentioning
confidence: 99%
“…Although optimal cluster characteristics vary forecast-to-forecast, results across all forecasts are examined to select a single combination of polynomial order and number of clusters to evaluate. For mixturemodel clustering of ensemble TC tracks, Kuruppumullage Don et al (2016) and Kowaleski and Evans (2016) found that selecting the optimal polynomial order is more straightforward than selecting the optimal number of clusters; therefore, we evaluate polynomial order first.…”
Section: Clustering Methodologymentioning
confidence: 99%
“…The total TC count for each cluster is indicated next to the cluster number. applications of this cluster analysis include a comparison of tracks of TCs in a reanalysis dataset to observations (Bell et al 2018), analysis of the skill of tropical cyclone forecasts (Don et al 2016, Kowaleski and, and in the development of statistical-dynamical seasonal forecasts (Zhang et al 2016). The application we focus on here is to examine the ability of climate models to simulate observed track types and if/how they change under anthropogenic climate change.…”
Section: E Tropical Cyclone Track Clustering Methodsmentioning
confidence: 99%
“…Kuruppumullage Don et al (2016) and Kowaleski and Evans (2016), using the method developed by Gaffney et al (2007). We focus on results from track clustering throughout the paper; CPS path clustering is performed to help select the optimal track cluster partition.…”
Section: Fig 5 Wrf Domains Used In All Simulations Of Hurricane Sandymentioning
confidence: 99%
“…Regression mixture-model clustering requires the selection of cluster shape, polynomial order, and number of clusters prior to clustering. All clusters are prescribed to have a circular error covariance matrix as in Kuruppumullage Don et al (2016) TABLE 1. Model configuration used in WRF, version 3.8, simulations of Hurricane Sandy.…”
Section: Fig 5 Wrf Domains Used In All Simulations Of Hurricane Sandymentioning
confidence: 99%
See 1 more Smart Citation